Cinética do comprometimento do sistema citocromo p-450 microssomal hepático na esquistossomose mansônica murina - Lais de Carvalho Maroni (2006)
Acute and chronic diseases, such as schistosomiasis, may affect the hepatic architecture or function, impairing liver detoxication function and drug metabolism. Objectives: To evaluate quantitative changes in enzymes of the cytochrome P-450 subfamilies 1A1, 2A6, 2B1, 2C11, 2E1, 3A2 and reductase, during the acute and chronic phases of schistosomiaisis and after treatment with oxamniquine by westernblot. To evaluate the kinetics of these changes in the subfamilies 1A1, 2E1 and 3A4 during the acute and chronic phases, by immuhistochemistry. Methods: Cytochrome P-450 isoenzymes expression was evaluated through western blotting and the kinetics of the alterations of the isoenzymes 1A1, 2E1 and 3A4 through immunohistochemistry. Results: The majority of cytochrome P-450 isoenzymes are altered during the infection by S. mansoni. However, some of them (e.g. CYP1A1) showed no modification of its levels of expression during the period studied and the expression of other (e.g. CYP3A4) showed an oscillatory pattern (as seen by immunohistochemistry), suggesting a specific modification in the microsomal hepatic enzymatic system in the course of S. mansoni infection. Conclusion: The infection by S. mansoni alters the hepatic microssomal expression of several cytochrome P-450 isoenzymes.